2021
DOI: 10.1093/mnras/stab2211
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Teff, radius, and luminosity of M-dwarfs using high-resolution optical and NIR spectral features

Abstract: We estimate effective temperature (Teff), stellar radius, and luminosity for a sample of 271 M-dwarf stars (M0V-M7V) observed as a part of CARMENES (Calar Alto high-Resolution search for M dwarfs with Exo-earths with Near-infrared and optical Echelle Spectrographs) radial-velocity planet survey. For the first time, using the simultaneously observed high resolution (R∼90000) spectra in the optical (0.52–0.96 μm) and near-infrared (0.96–1.71 μm) bands, we derive empirical calibration relationships to estimate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…It cannot be excluded that these deviations contribute to the disagreements in derived stellar parameters found in this work. However, we were able to shed some light on deficiencies of some methods, for instance, showing that the DL method would benefit from the use of multiple wavelength ranges and that ODUSSEAS could improve the T eff determination by using different sets of lines or, most importantly, by using a new reference T eff scale based on interferometry (Khata et al 2021). This possibility is currently being explored and is expected to be implemented as an option in an upgraded version of the tool.…”
Section: Discussionmentioning
confidence: 97%
“…It cannot be excluded that these deviations contribute to the disagreements in derived stellar parameters found in this work. However, we were able to shed some light on deficiencies of some methods, for instance, showing that the DL method would benefit from the use of multiple wavelength ranges and that ODUSSEAS could improve the T eff determination by using different sets of lines or, most importantly, by using a new reference T eff scale based on interferometry (Khata et al 2021). This possibility is currently being explored and is expected to be implemented as an option in an upgraded version of the tool.…”
Section: Discussionmentioning
confidence: 97%
“…For the very high resolutions of ESPRESSO and HARPS, the results derived by ODUSSEAS are essentially the same either by using directly the original highest-resolution spectra of ESPRESSO, or by convolving first the ESPRESSO spectra to the lower, but still high, resolution of HARPS. We ran ODUSSEAS by considering a reference data set composed of 47 stars with interferometry-based T eff (Rabus et al 2019;Khata et al 2021), and [Fe/H] derived through the photometric calibration by Neves et al (2012) using the Gaia DR3 parallaxes. We obtain T eff = 3419 ± 92 K and [Fe/H] = −0.03 ± 0.11 dex.…”
Section: Stellar Atmospheric Parametersmentioning
confidence: 99%
“…The modeling of M dwarfs has advanced in recent years. Several works adopting high-resolution spectrum synthesis techniques (Lindgren et al 2016;Lindgren & Heiter 2017;Souto et al 2017Souto et al , 2018bSouto et al , 2020Souto et al , 2022Veyette et al 2017;Passegger et al 2018Passegger et al , 2019aPassegger et al , 2019bPassegger et al , 2020aPassegger et al , 2020bRajpurohit et al 2018aRajpurohit et al , 2018bLópez-Valdivia et al 2019;Birky et al 2020;Khata et al 2021;Marfil et al 2021;Sarmento et al 2021) have demonstrated that reliable stellar parameters for M dwarfs can be obtained, although there are certainly systematic differences between the metallicity results that still need to be evaluated in detail. The study of M dwarfs in open clusters as benchmarks offers the possibility to test the metallicity scale as a function of the M-dwarf effective temperature and also quantify possible systematic metallicity differences between the M dwarfs and the hotter FGK stars.…”
Section: Introductionmentioning
confidence: 99%